The Role Of Ganoderma Lucidum In The Prevention Of Cancer (Texas Journal of Medical Science, 2025)
Today, oncological diseases are observed in infants and the elderly. An important place is occupied by early detection of the development of oncological diseases, the use of effective methods of treatment and prevention. When treating a patient diagnosed with cancer, it is important not only to use therapeutic measures, but also to take into account the psychology of the patient. This article provides information on drugs prepared from ganoderma for the prevention of oncological diseases